Modul Ajar berbasis Kearifan Lokal Tema 4 Berbagai Pekerjaan Kelas IV di Sekolah Dasar - Dita Eka Putri Dewanti; Dessy Setyowati; Muhammad Aqmal Nurcahyo (Edu Berkah Khatulistiwa, 2023)
Research on the development of teaching modules based on local wisdom, theme 4, various job in elementary schools grade IV has been carried out at SDN 08 Sungai Raya. The subjects of this study were 22 students of class IV B. The research method used was research and development or Research and Development using the ADDIE model. Data collection techniques were carried out using validation sheets, questionnaires and questions. The validation results from linguists obtained an average percentage of 93% with very good criteria, the assessment results from material experts obtained an average percentage of 80% with good criteria and the assessment results from design experts obtained an average percentage of 83% with the criteria Very good. The results of the student response questionnaire for the small group trial with a total of 9 students obtained an assessment result of 93% which was very good and the results for the large group trial with a total of 22 students obtained an assessment result of 91% which was very good. The results of the large group trial with a total of 22 students obtained a high value of 0.81. Based on the results of this study, it can be concluded that the teaching modules based on local wisdom, theme 4, various class IV jobs in this elementary school can be used as one of the teaching materials at SDN 08 Sungai Raya.